On Oscillation of Second Order Damped Nonlinear Differential Equations (المجلة العلمية لكلية التربية, 2025)
This article introduces novel criteria for analyzing the oscillatory patterns exhibited by the solutions of damped differential equations. The main results we are derived through the utilization of crucial techniques, such as the Riccati method and integral averaging. The theorems presented in this study offer a more comprehensive and extended approach than compared to prior research. Illustrative examples are included to highlight the distinctions between our findings and those documented in existing literature.
Keywords: oscillatory behaviour; damped differential equations.; second order